2017
DOI: 10.3389/fpls.2017.01425
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-Induced Toxicity Is Counteracted by Sulfur in Broccoli (Brassica oleracea L. var. italica)

Abstract: Selenium (Se) is an essential micronutrient for humans. Increasing Se content in food crops offers an effective approach to enhance the consumption of Se in human diets. A thoroughly understanding of the effects of Se on plant growth is important for Se biofortification in food crops. Given that Se is an analog of sulfur (S) and can be toxic to plants, its effect on plant growth is expected to be greatly affected by S nutrition. However, this remains to be further understood. Here, we evaluated the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Cd toxicity negatively affects photosynthesis by reducing chlorophyll content, which adversely influences general plant growth and development by disrupting vital metabolic processes (Kim et al, 2008;Hong et al, 2013;Jan et al, 2015;Khan et al, 2015;Jung et al, 2016Jung et al, , 2017Jung et al, , 2018bFarooq et al, 2018). Recently, some studies have demonstrated that the exogenous application of sulfur (Khan et al, 2015;Jung et al, 2017;Tian et al, 2017), glutathione (Chen et al, 2010;Mostofa et al, 2014;Kim et al, 2017;Jung et al, 2019) or ascorbate (Chen et al, 2017;Jung et al, 2018a;Semida et al, 2018;Zhang et al, 2019) may alleviate different heavy metal stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Cd toxicity negatively affects photosynthesis by reducing chlorophyll content, which adversely influences general plant growth and development by disrupting vital metabolic processes (Kim et al, 2008;Hong et al, 2013;Jan et al, 2015;Khan et al, 2015;Jung et al, 2016Jung et al, , 2017Jung et al, , 2018bFarooq et al, 2018). Recently, some studies have demonstrated that the exogenous application of sulfur (Khan et al, 2015;Jung et al, 2017;Tian et al, 2017), glutathione (Chen et al, 2010;Mostofa et al, 2014;Kim et al, 2017;Jung et al, 2019) or ascorbate (Chen et al, 2017;Jung et al, 2018a;Semida et al, 2018;Zhang et al, 2019) may alleviate different heavy metal stresses.…”
Section: Discussionmentioning
confidence: 99%
“…As toxicity affects photosynthesis by reducing the chlorophyll content, which negatively influences general plant growth and important metabolic processes, and by inhibiting adenosine triphosphate (ATP) biosynthesis by disrupting phosphorus uptake in the roots (Panda et al, 2010; Finnegan and Chen, 2012; Gupta and Ahmad, 2014; Jung et al, 2017b). Recently, some studies have demonstrated that the exogenous application of hydrogen sulfide (Singh et al, 2015b; Li et al, 2016; Chen et al, 2017), sulfur (Khan et al, 2015; Jung et al, 2017a; Tian et al, 2017), AsA (Jung et al, 2018; Semida et al, 2018), or GSH (Shri et al, 2009; Chen et al, 2010; Mostofa et al, 2014; Kim et al, 2017) may alleviate different heavy metal stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Se shares similar metabolic pathways in plants with sulfur (S) because of their chemical and physical similarities (Shinmachi et al, 2010 ; Tian et al, 2017 ). There are two key enzymes involved in Se metabolism pathways: ATP sulfurylase (ATPS) and selenocysteine methyltransferase (SMT).…”
Section: Microelements and Their Genetic Regulation Via Transgenic Apmentioning
confidence: 99%